Associations between ponderal index and hypothalamic mean diffusivity in typically developing 5-year-olds - Ståhlberg, Emilia (My University, 2025)
Childhood overweight and obesity are growing concerns, particularly in Western countries. The World Health Organization (WHO) has identified childhood overweight as one of the most significant global health risks. Childhood obesity has long-term consequences, including an increased risk of obesity and related conditions, such as type 2 diabetes, in adulthood. This study investigates the relationship between body weight and hypothalamic structure in 5-year-old Finnish children. The data were collected from the FinnBrain birth cohort study. The FinnBrain birth cohort study is a large, multidisciplinary longitudinal study examining the effects of environmental and genetic factors on child development and health. The study recruited 3,808 pregnant women between 2011 and 2015 from the regions of Southwest Finland and Åland. The children born into the study and their families have been followed using various research methods from pregnancy to later childhood. This study specifically examined the association between the ponderal index and the mean diffusivity (MD) value of the hypothalamus in 5-year-old children. In this cross-sectional study, 147 mother-child pairs were randomly recruited, all of whom had available brain MRI scans at the age of 5 years. The children were born between 2012 and 2015, and 53% of them were boys. Sociodemographic variables were obtained from cohort study questionnaires and national registers. The sample is representative of the general Finnish population. Written informed consent was obtained from the parents for both themselves and their child, and the child’s assent was also ensured before the research visits. This study examines how childhood overweight and obesity, as well as maternal pre-pregnancy BMI, influence brain structure. The hypothesis is that a higher maternal pre-pregnancy BMI is associated with increased mean diffusivity in the child's hypothalamus. The findings of this study provide direction for future research to further investigate the causes and consequences of childhood overweight and obesity.

Lasten ylipaino ja lihavuus ovat kasvava huolenaihe erityisesti länsimaissa. Maailman terveysjärjestö (WHO) on listannut lasten ylipainon yhdeksi merkittävimmistä maailmanlaajuisista terveysriskeistä. Lapsuusiän lihavuudella on pitkäkantoisia vaikutuksia niin aikuisiän lihavuuteen sekä liitännäissairauksiin kuten tyypin 2 diabetekseen. Tässä tutkimuksesta tutkitaan 5-vuotiaiden suomalaislasten painon yhtettä hypotalamuksen rakenteeseen. Data kerättiin FinnBrain syntymäkohortin aineistosta. FinnBrain-syntymäkohorttitutkimus on laaja monitieteellinen seurantatutkimus, jossa tutkitaan ympäristön ja perimän vaikutusta lapsen kehitykseen ja terveyteen. Tutkimukseen rekrytoitiin 3808 raskaana olevaa vuosina 2011–2015 Varsinais-Suomen ja Ahvenanmaan alueelta. Syntyneitä lapsia sekä perheitä on seurattu erilaisin tutkimusmenetelmin raskaudesta myöhempään lapsuuteen saakka. Tässä tutkimuksessa tutkittiin 5-vuotiaiden lapsien ponderaalisen indeksin ja hypotalamuksen MD-arvon (keskimääräinen diffuusiivisuus) yhteyttä. Tässä poikkileikkaustutkimuksessa satunnaisesti rekrytoitiin 147 äiti-lapsi-paria, joilla oli käytettävissä aivojen MRI-kuvaus 5 vuoden iässä. Lapset olivat syntyneet vuosina 2012–2015, ja heistä 53 % oli poikia. Sosiodemografiset muuttujat saatiin kohorttitutkimuksen kyselylomakkeista sekä kansallisista rekistereistä. Otos vastaa hyvin Suomen väestön yleisiä piirteitä. Vanhemmat antoivat kirjallisen, tietoisen suostumuksen sekä itsensä että lapsensa puolesta, ja lisäksi varmistettiin lapsen suostumus ennen tutkimuskäyntejä. Tässä tutkimuksessa tutkitaan miten lapsuuden ylipaino ja lihavuus sekä äidin raskautta edeltävän BMI vaikututtavat aivojen rakenteeseen. Hypoteesina on, että äidin korkeampi raskautta edeltävä BMI nostaisi lapsen hypotalamuksen keskimääräistä diffusiviteettia. Tämän tutkimuksen tuloksilla annetaan suuntaa tuleville tutkimuksille, jotta voidaan selvitettää lapsuuden ylipainon ja lihavuuden syitä ja seurauksia.
Keywords: childhood, overweight, obesity, neuroimaging, hypothalamus, lapsuus, ylipaino, lihavuus, aivokuvantaminen, hypotalamus